Effect of force direction and masticatory force towards orthodontic tooth movement in rats - Farmasyanti, Cendrawasih Andusyana; Maulani, Adibah (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
The aim of the research is to investigate the influence of coil spring directions and masticatory force on the amount of OTM. Materials and Methods. Thirty-six male Wistar rats (n = 36) were divided proportionally into two groups with (M) or without masticatory force (NM), treated with palatal coil type (PD) or labial coil (LD) using a costumed stainless steel coil spring to deliver 35 cN force for separating the two incisors in 10 days. The examination dates were day 0, day 5, and day 10. The tooth distance values were calculated by subtracting the distance measured at day 0 from examination days and presented in 8 groups: PD5NM, PD10NM, PD5M, PD10M, LD5NM, LD10NM, LD5M, and LD10M. The study’s results were analyzed using ANOVA followed by post hoc analyses. Result: All spring designs induced OTM. The OTM amounts from the lowest to the highest are PD5M, PD10NM, PD10M, LD5M, LD10M, LD5NM, PD5NM, and LD10NM, respectively: 0.26 mm; 0.06 mm; 0.25 mm; 0.44 mm; 0.58 mm; 0.9 mm; 0.97 mm; 1.03 mm, and 1.06 mm. The OTM distance was higher in the labial coil than in the palatal coil groups (p = 0.002). The amount of OTM in the masticatory group was lower than in the group without-masticatory force (p = 0.012), except in the day 10 palatal coil group. Conclusions: Masticatory force and force direction affected the amount of OTM. The labial coil induces more OTM than the palatal coil. Masticatory force decreased the OTM distance.